2017
DOI: 10.1371/journal.pone.0178164
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic dissection reveals wide spread differential expression in chickpea during early time points of Fusarium oxysporum f. sp. ciceri Race 1 attack

Abstract: Plants’ reaction to underground microorganisms is complex as sessile nature of plants compels them to prioritize their responses to diverse microorganisms both pathogenic and symbiotic. Roots of important crops are directly exposed to diverse microorganisms, but investigations involving root pathogens are significantly less. Thus, more studies involving root pathogens and their target crops are necessitated to enrich the understanding of underground interactions. Present study reported the molecular complexiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 121 publications
1
12
0
Order By: Relevance
“…The results of transcriptome meta-analysis along with machine-learning weighting confirmed the importance of PSAG and LHCA2 in adaptation responses to salt stress condition ( Table 2 ). It has been proposed that salt stress weakens the connection between LHCs and PSI and consequently reduces the conversion of light energy to chemical energy (Gupta et al, 2017). Our hypothesis has been also confirmed by recent study (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of transcriptome meta-analysis along with machine-learning weighting confirmed the importance of PSAG and LHCA2 in adaptation responses to salt stress condition ( Table 2 ). It has been proposed that salt stress weakens the connection between LHCs and PSI and consequently reduces the conversion of light energy to chemical energy (Gupta et al, 2017). Our hypothesis has been also confirmed by recent study (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of rbcL, HSP90A, and LHC in the PPI network was also consistent with previous findings (Wang et al, 2019). It has also been found that chlorophyll a–/b–binding proteins such as LHCA2 are affected by light, oxidative stress, and chlorophyll retrograde signaling (Gupta et al, 2017). Downregulation of LHC under the stress condition corroborates these earlier finding that downregulation of the LHC under stress conditions is an attempt to minimize energy utilization by lowering photosynthetic demands (Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In legumes, this gene class has been pointed out as responsible for resistance against the nematode Heterodera glycines [75]. The expression levels of LOC101510206 is an interesting finding as another locus from the same family mapped onto chromosome 8 has been found to be regulated in chickpea during Foc1 attack [17].…”
Section: Resultsmentioning
confidence: 99%
“…Plants adapt to water stress condition by increased concentration of intracellular solutes, such as proline, which facilitate the maintenance of cell pressure potential 34 . Moreover, role of proline as osmoprotectant in plant defense against invading pathogen has earlier been documented 35 , 36 . We observed that WR-315 was able to maintain Relative Water Content (RWC) considerably at higher level while JG-62 showed the maximum decline, suggesting inability of susceptible genotype to take up water due to maximum colonization of the pathogen in the xylem (Fig.…”
Section: Resultsmentioning
confidence: 99%